2009
DOI: 10.1002/elan.200904606
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 5‐Aminosalicylic Acid by Catalase‐Peroxidase Based Biosensor

Abstract: 5-Aminosalicylic acid is an antiinflammatory drug used to treat inflammation of the digestive tract (Crohns disease) and mild to moderate ulcerative-colitis. 5-Aminosalicylic acid is a bowel-specific aminosalicylate drug. It was developed an amperometric biosensor for determination of 5-aminosalicylic acid concentration and measurement technique is based on substrate-competition. The biosensor is more suitable especially for routine 5-aminosalicylic acid analysis because it is simple to construct and sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In comparison, electrochemical sensors and biosensors have some advantages such as high sensitivity, inexpensive equipments, simple modification of working electrodes and they can be used in “in vivo” and “in situ ” biological studies. To our knowledge, in the recent years limited number of studies can be found in literature on electrochemical determinations of MSA 2428.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, electrochemical sensors and biosensors have some advantages such as high sensitivity, inexpensive equipments, simple modification of working electrodes and they can be used in “in vivo” and “in situ ” biological studies. To our knowledge, in the recent years limited number of studies can be found in literature on electrochemical determinations of MSA 2428.…”
Section: Introductionmentioning
confidence: 99%
“…Catalase and horseradish peroxidase were co-entrapped in a gelatin matrix to prepare a biosensor on the surface of a Teflon thin membrane covering a gold electrode for the determination of 5-aminosalicylic acid. The biosensor retained 91 % of its activity after 21 days of storage at 4 C in a wet atmosphere [30].…”
Section: Immobilization Techniquesmentioning
confidence: 99%
“…In 2011, electrochemical sensors for the paracetamol were also reported. In 2009, Akkaya et al [143] reported a catalase-peroxidase-based biosensor for the determination of 5-aminosalicylic acid (5-ASA, mesalazine), which is an antiinflammatory drug used to treat inflammation of the digestive tract (Crohn's disease). The LOD obtained was 2.5 nM in buffer.…”
Section: Analgesics and Anti-inflammatory Compoundsmentioning
confidence: 99%